Pendampingan Kemampuan Membaca Al-Qur’an Melalui Makharijul Huruf Dengan Metode Sorogan di TPQ Al-Hikmah Dsn. Sekuning Desa Besowo - Auliyatul Faizah Diah Khalwati (LP3M IAIFA Kediri, 2023)
The Qur’an is a kalam of Allah that was handed down to the Prophet Muhammad SAW through the intermediary of the angel Gabriel to mankind to be used as a guide in life in the world and in the hereafter and reading the holy book of the Qur’an is a worship. As Muslims, it is an obligation to read, understand, practice and teach the holy book of the Qur’an to other Muslims. And reading the Qur’an it must be tartil, Tartil according to language means to displace, beautify and land-land. However, to be able to read the holy book of the Qur’an with ntartil it is necessary to learn the knowledge of tajwid, especially about makharijul letters which is the first step to read the holy book of the Qur'an. Hijaiyah letters are arabic spelling letters as the original language of the Qur’an, in hijaiyah letters there are differences in pronunciation between one letter and another. Departing in this case is very much needed with a companion for smoothness and maximality in learning the makharijul of the letter. The term mentoring according to the Big Indonesian Dictionary (KBBI) comes from the word damping which means close, close, meeting. While mentoring is a process, a way of accompanying or accompanying. Mentoring is social mentoring which is a strategy that greatly determines the success of community empowerment programs. Reading the Qur’an in accordance with the tajwid of his law fardhu ain and studying the science of tajwid his law fardu kifayah. The person who is obliged to teach the Qur’an is the one who reads it best in his environment, although it is not so good compared to others in the other environment”. Using the knowledge of tajwid correctly or eloquently according to what was taught by the Prophet Muhammad SAW, in order to be able to maintain the orality of mistakes when reading the Qur’an. The purpose of